EARLY AND LATE COMPLICATIONS FOLLOWING VISION CORRECTION WITH SMILE AND LASIK METHODS. ANALYSIS OF DIFFERENCES - Sara Langner; Ewa Katarzyna Malaka; Martyna Byrska; Marlena Zubiak; Hanna Barska-Kobylińska; Marta Janura; Eliza Kawalska; Maciej Borowski; Jakub Motor; Alicja Grzelak (International Journal of Innovative Technologies in Social Science, 2025)
Vision correction through refractive surgical procedures has become increasingly precise and patient-specific, with SMILE (Small Incision Lenticule Extraction) and LASIK (Laser-Assisted in Situ Keratomileusis) emerging as two of the most commonly performed techniques for the treatment of myopia and astigmatism. Both methods offer excellent visual outcomes and rapid postoperative recovery; however, they differ significantly in terms of surgical approach, which in turn influences the profile and frequency of complications. This review explores and compares the complications associated with each procedure, highlighting key differences in both early and late postoperative outcomes.Early complications such as dry eye syndrome, transient visual disturbances, and epithelial healing irregularities tend to occur more frequently after LASIK. This is likely due to the creation of a corneal flap in LASIK, which can disrupt more corneal nerves and tissues. In contrast, SMILE, which involves only a small peripheral incision without a flap, preserves more of the corneal architecture, leading to a reduced incidence of postoperative dryness and inflammation.Furthermore, long-term complications, including corneal ectasia, appear to be less prevalent following SMILE, likely owing to the better biomechanical stability maintained in the cornea. A nuanced understanding of these complication patterns is essential for clinicians to select the most appropriate technique based on individual patient characteristics, ocular anatomy, and lifestyle demands. Tailoring the surgical approach not only improves clinical outcomes but also helps in minimizing procedural risks and enhancing patient satisfaction.